Determination of Bromate at Trace Level in Sudanese Bottled Drinking Water Using Ion Chromatography - Mei Musa; Ibrahim M. Ahmed; Ismat Atakruni (E-Journal of Chemistry)
Bromate ion was determined by ion chromatography with spectro-photometric detection after post column reaction with o-dianisidine reagent in acidic medium. IonPac AS19 anion-exchange column was used with 20 mM sodium hydroxide eluent. The eluent from the column was then allowed to react with o-dianisidine at 60 °C. The developed colour of the final product was measured spectrophotometrically at 450 nm. Linearity of the method was checked up to 200 μg/L by using 200 μL sample injection volume and the linear correlation coefficient was 0.9998. The method detection limit was 0.56 μg/L and the precision was 6.2% at 100 μg/L. The spiked recovery for bromate in water samples was 93%. Interferences from some anions eg. nitrate, chloride and nitrite were studied. The method was applied for the determination of bromate ion in ten sudanese bottled drinking water. Bromate was detected in 60% of the samples at concentrations ranged between 5-169 μg/L.